Torque ripple alleviation of a five-phase permanent magnet synchronous motor using predictive torque control method - Saif Talal Bahar; Riyadh G. Omar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The benefits of a five-phase permanent magnet synchronous motor (five-phase-PMSM) are its compact size, high fault tolerance, low voltage, and high output. The drives of this kind of machines can be enhanced using model predictive torque control (MP-DTC) technique. The outcomes of this technique with additional weighting factors are reduces the complexity of calculation, and reduction in current harmonics, which present in harmonic subspace in standard model predictive torque control. Decrease the low-order harmonic constituents of stator currents and alleviation torque ripple can be achieved by optimizing the objective function. Adding current limitations and switching frequency-weighting factor improves the cost function. The suggested technique can provide superior steady-state performance and keep the quick transient performing as a possible characteristic of the MP-DTC scheme. Thus, with the advantageous steady state and dynamic performing obtained concurrently, the most important aspects of the suggested system are the reduced mathematical burden, and with simplified objective functions compared to classic MP-DTC structure. The proposed method reduced the torque ripple from (3.49%) in a traditional method to (0.58%).